EXAMPLES OF FINDING FUNCTION LIMITS - Zevarjon Rustamboyevna Jumaboyeva (Bright Mind Publishing, 2025)
This article analyzes the domains, formulas, and properties of several important functions in mathematical analysis. For each function, the domain is clearly defined, and some are studied in depth from the perspective of limits. The article serves as a useful methodological guide for students and teachers within the scope of the mathematical analysis course.
Keywords: Function, limit, domain, trigonometric function, exponential function, remarkable limits, mathematical analysis.